Optimization of EDM Small Hole Drilling Process Using Taguchi Approach - M. F. F., Ab Rashid; W. S., Wan Harun; S. A., Che Ghani (Asian Research Publishing Network (ARPN), 2016)
Electrical Discharge Machining (EDM) is a process used to remove or cut a material into desired shape through the action of spark discharge between the tool and work piece. The objective of this paper is to optimize the independent variables to achieve better accuracy in EDM small hole drilling by using Taguchi method. The L9 orthogonal array is employed to study the performance characteristics in drilling operations of mild steel (AS3679) as workpiece by using 1 mm copper (Cu) pipe electrode. Three drilling parameters namely, pulse off time, peak current and servo standard voltage are considered to optimize drilling hole diameter. The result concluded that use of greater pulse off time, greater peak current and medium servo standard voltage give the better hole diameter for the specific test range. Further study in this topic could consider different factor such as pulse on time, material removal rate (MRR) and coolants to investigate how these factors would affect hole diameter